Who Benefits from Universal Child Care? Estimating Marginal Returns to Early Child Care Attendance - Thomas Cornelissen; Christian Dustmann; Anna Raute; Uta Schönberg (Institute of Labor Economics (IZA), 2018)
In this paper, we examine the heterogeneous treatment effects of a universal child care (preschool) program in Germany by exploiting the exogenous variation in attendance caused by a reform that led to a large staggered expansion across municipalities. Drawing on novel administrative data from the full population of compulsory school entry examinations, we find that children with lower (observed and unobserved) gains are more likely to select into child care than children with higher gains. This pattern of reverse selection on gains is driven by unobserved family background characteristics: children from disadvantaged backgrounds are less likely to attend child care than children from advantaged backgrounds but have larger treatment effects because of their worse outcome when not enrolled in child care.
Keywords: J13; J15; I28; 330; universal child care; child development; marginal treatment effects